A new design of CAD/CAM surgical template system for two-piece narrowing genioplasty. Issue 5 (May 2016) - Li, B.; Shen, S.G.; Yu, H.; Li, J.; Xia, J.J.; Wang, X.
Abstract: The purpose of this study was to develop and validate a new chin template system for a two-piece narrowing genioplasty. Nine patients with wide chin deformities were enrolled. Surgeries were planned with the computer-aided surgical simulation (CASS) planning method. Surgical splints and chin templates were designed in a computer and fabricated using a three-dimensional printing technique. The chin template system included a cutting guide and a repositioning guide for a two-piece narrowing genioplasty. These guides were also designed to avoid the mental foramen area and inferior alveolar nerve loops during the osteotomy, for nerve protection. After surgery, the outcome evaluation was completed by first superimposing the postoperative computed tomography model onto the planned model, and then measuring the differences between the planned and actual outcomes. All surgeries were completed successfully using the chin template system. No inferior alveolar nerve damage was seen in this study. With the use of the chin templates, the largest linear root mean square deviation (RMSD) between the planned and the postoperative chin segments was 0.7 mm and the largest angular RMSD was 4.5°. The results showed that the chin template system provides a reliable method of transfer for two-piece osseous narrowing genioplasty planning.